Design of Catalase Monolithic Tablets for Intestinal Targeted Delivery - Mirna Alothman; Pompilia Ispas-Szabo; Mircea Alexandru Mateescu (MDPI AG, 2021)
Several studies confirmed a correlation between elevated hydrogen peroxide (H2O2) levels in patients with intestinal bowel diseases (IBD) and the negative effects caused by its presence. The objective of this study was to explore the potential use of catalase (CAT) to diminish the level of H2O2 and its deleterious action on intestinal mucosa. Oral dosage forms of a CAT bioactive agent targeted to the intestines were designed and tested in various simulated gastric and intestinal media. Monolithic tablets (30% loading) were prepared using commercial CarboxyMethylCellulose (CMC) or synthesized CarboxyMethylStarch (CMS) and TriMethylAmineCarboxyMethylStarch (TMACMS) as matrix-forming excipients. For starch derivatives, the presence of the ionic groups (carboxymethyl and trimethylamine) was validated by spectral analysis. In vitro studies have shown that tablets formulated with TMACMS and 30% CAT resisted the acidity of the simulated gastric fluid and gradually released the enzyme into the simulated intestinal fluid. The investigation of the CAT release mechanism revealed the role of anionic and cationic groups of polymeric excipients and their involvement in the modulation of the CAT dissolution profile. The proposed drug delivery system can be considered an efficient solution to target CAT release in the intestine and contribute to the reduction of H2O2 associated with intestinal inflammation.